2014
DOI: 10.1111/bju.12649
|View full text |Cite
|
Sign up to set email alerts
|

Phase III, randomised, double‐blind, placebo‐controlled study of the β3‐adrenoceptor agonist mirabegron, 50 mg once daily, in Japanese patients with overactive bladder

Abstract: Registered at clinicaltrials.gov (NCT00966004). Objective• To evaluate the efficacy and safety of the β3-adrenoceptor agonist mirabegron, in a Japanese population with overactive bladder (OAB). Patients and Methods• This randomised, double-blind, placebo-controlled phase III study enrolled adult patients experiencing OAB symptoms for ≥24 weeks. Patients with ≥ 8 micturitions/24 h and ≥1 urgency episode/24 h or ≥1 urgency incontinence episode/24 h were randomised to once-daily placebo, mirabegron 50 mg or tolte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
172
2
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(191 citation statements)
references
References 35 publications
(41 reference statements)
13
172
2
4
Order By: Relevance
“…Mirabegron is the first β3 agonist to be used in clinical practice. [50][51][52][53] (D) To assess the efficacy and tolerability of this drug therapy in the treatment of idiopathic overactive bladder (IOAB), two phase II 54,55 (B) and six phase III [56][57][58][59][60][61] (A) randomized clinical trials (RCTs) recruited more than 10,500 adult patients. Of these, seven were randomized, double-blind and placebo-controlled with follow-up of four (one study) and 12 (six studies) weeks, and one was non-placebo-controlled (vs. tolterodine) with 12-month follow-up.…”
Section: Tolterodine Tartratementioning
confidence: 99%
“…Mirabegron is the first β3 agonist to be used in clinical practice. [50][51][52][53] (D) To assess the efficacy and tolerability of this drug therapy in the treatment of idiopathic overactive bladder (IOAB), two phase II 54,55 (B) and six phase III [56][57][58][59][60][61] (A) randomized clinical trials (RCTs) recruited more than 10,500 adult patients. Of these, seven were randomized, double-blind and placebo-controlled with follow-up of four (one study) and 12 (six studies) weeks, and one was non-placebo-controlled (vs. tolterodine) with 12-month follow-up.…”
Section: Tolterodine Tartratementioning
confidence: 99%
“…Recent Phase III trials have confirmed the efficacy and safety of mirabegron in treatment of OAB [6970717273]. A urodynamic study in men with OAB and BOO revealed that mirabegron did not adversely affect the maximum flow rate (Qm ax ) and detrusor pressure at Q max after 12 weeks of treatment [74].…”
Section: Mirabegron Is Safe In Elderly Oab Patients Without Increamentioning
confidence: 99%
“…First-generation b3AR agonists were inadequately selective, and the second generation, although more selective, demonstrated poor oral bioavailability and pharmacokinetics [63]. Mirabegron, a drug that induces smooth muscle relaxation, is the only b3AR compound that has advanced to phase III clinical trials, but only for the treatment of overactive bladder [64,65]; effects on weight have not been assessed, and weight loss has not been reported as adverse event, although it has been recently reported that mirabegron induced BAT activation and increased EE [66].…”
Section: Sympathomimeticsmentioning
confidence: 99%